STRUCTURE OF THE MODEL FOR THE DEVELOPMENT PROJECT CULTURE OF VOCATIONAL TEACHERS (Innovative professional education, 2024)
The structure of the model for the development of the project culture of vocational teachers is substantiated, which includes the following blocks: conceptual and target, subjective, content and activity, diagnostic and reflective. The value of the model for the professional growth of the individual and the effective participation of vocational teachers in project activities to address the strategic objectives of the education sector and the quality of vocational training of students is summarized.
Keywords: model, project culture, vocational teacher, project activity